Structure of neutron-rich odd-mass127,129,131in populated in the decay of127,129,131Cd - Arndt, O; Hennrich, S; Hoteling, N; Jost, C; Tomlin, B; Shergur, J; Kratz, K; Mantica, P; Brown, B; Janssens, R; Walters, W; Pfeiffer, B; et al. (2009)
New level structures are proposed for neutron-rich127,129,131In populated in the decay of127,129,131Cd. No evidence for the presence of 1-particle- 2-hole intruder structures in the neutron-rich In isotopes is observed.